THE MIND CRITICISM IN POST-MODERN CONCEPSIONS - Грицай, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The  article  presents  the  analysis  of  postmodern  strategies  of  mind  criticism  which  try  to  rehabilitate  mind  denying  metaphysics, pluralization and decentralization of rationality.